Template‐Free Electrodeposition of SnSi Nanowires from an Ionic Liquid. Issue 9 (7th May 2015) - Elbasiony, Amr M.; Olschewski, Mark; El Abedin, Sherif Zein; Endres, Frank
Abstract We report the template‐free electrodeposition of SnSi nanowires from the ionic liquid 1‐butyl‐1‐methylpyrrolidinium trifluoromethylsulfonate, [Py1, 4]TfO, containing SnCl2 and SiCl4. The electrochemical behavior of the employed electrolyte was investigated by using cyclic voltammetry. The obtained nanowire films were characterized by SEM/EDX, XRD, UV spectroscopy, and XPS. The results show that freestanding and hair‐like SnSi nanowires can be obtained through potentiostatic electrodeposition at different potentials after running cyclic voltammetry. The XPS and EDX results reveal the composition of the films and show that SnSi co‐deposits are formed. XRD patterns indicate the formation of amorphous Si and no clear indication of the formation of a SnSi alloy. The band gap of the deposited film was determined from the UV spectrum to be 1.55 eV.